Rituals of mediation : international politics and social meaning / François Debrix and Cynthia Weber, editors. - Debrix, François; Weber, Cynthia (University of Minnesota Press, 2003)
The authors consider international issues like security, development, political activism, and the war against terrorism through the lens of cultural practices such as traveling through airports, exhibiting art and photography, logging on to the Internet, and spinning news stories.